K+ Nutrition Exchange in the Serendipita-Arabidopsis Symbiosis: Study of the Fungal K+ Transporters Involved - Conchillo, Lorena B.; Haro, Rosario; Benito, Begoña (Frontiers in Ecology and Evolution, 2021)
There is mounting evidence that the root-colonizing endosymbiotic fungus Serendipita indica improves plant growth. The beneficial effects have been observed when plants are growing in optimal conditions or under nutritionally deficient soils (e.g., phosphate poor soil) or exposed to stressful environmental conditions such as drought or salinity. However, until now its role in the nutrition of other plant essential macronutrient, such as K+, has not been fully clarified. Here, we study the role of the fungus in the K+ nutrition of Arabidopsis thaliana plants, during growth under K+ limiting conditions. As a first step, we studied the high-affinity K+ uptake of the plant and fungus when growing separately and in symbiosis. In the search for putative fungal actors involved in K+ nutrition, we also have cloned and functionally characterized the K+ transporters of S. indica SiHAK1, SiTRK1, SiTRK2 and SiTOK1, among which it has been shown that SiHAK1 is the main transporter involved in the K+ uptake in the high affinity range of concentrations. In addition, a gene expression study of these transporters and other candidates that could participate in the K+ homeostasis of the fungus has been carried out. The results indicated that, contrary to what happens with P nutrition, S. indica seems not to improve neither the growth nor the plant K+ reserves during K+ starvation. Instead, this nutritionally restrictive condition favored fungal colonization, suggesting that the fungus obtains the greatest benefit in K+ supply during symbiosis.